Controlling Stereoselectivity in Tribromide Mediated Oxidative Dearomatisations – Synthesis of Selective Spirofurano‐naphthalones. Issue 34 (23rd August 2019) - Sarkar, Debayan; Kuila, Puspendu; Sood, Devashish
Abstract : A series of ammonium tribromides were screened for exploring the role of ammonium counterpart attached to tribromides on generation of stereoselective spiro‐furans via oxidative dearomatisation of naphthols. The proposition enlightens a suitable combination of the ammonium tribromide and solvent employed, deliver the best achieved diastereoselectivities. This in turn, has also envisioned the mechanistic aspects related to this category of reactions. The mentioned dearomative spiro‐furano naphthalones has also been successfully achieved on a large‐scale. Abstract : A mild and highly stereocontrolled tribromide mediated synthesis of spiro‐furano naphthalones via a oxidative dearomatisation process is reported.